The Effect of Company Size and Financial Distress on Going Concern Audit Opinions with Opinion Shopping as Moderation Variables - Fransisca Listyaningsih Utami; Yuha Nadhirah Qintharah (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study aims to examine the effect of  company size and financial distress on going concern audit opinions with opinion shopping as moderation variables. The population in this study are companies with types of manufacturing industries listed on the Indonesia Stock Exchange in the period 2016 to 2018. The sample was obtained using a purposive random sampling method. Data analysis uses logistic regression and different absolute values. The results showed that company size and financial distress affected going concern audit opinions, opinion shopping did not affect company size on going concern audit opinions and opinion shopping affected financial distress on going concern audit opinions.